An investigation of the antecedents to cooperative marketing strategy implementation - Dickinson, Sonia; Ramaseshan, Balasubramanian (Taylor and Francis, 2004)
Firms make decisions about the most favourable strategy to implement, given that they face a set of environmental conditions. Interorganisational arrangements (IOAs) are a single strategic response that can potentially contribute to continuing and considerable performance outcomes, although it is recognised that this is not an isolated performance solution. It is, however, important to understand the reasons why firms engage in IOAs and to ascertain the environmental conditions that would be ideal for such arrangements. Specifically, this paper aims to identify the antecedents that motivate firms to engage in a functional form of IOA, namely, cooperative marketing. That is, it seeks to appraise the internal and external contexts under which there is a need for cooperative marketing strategies.